SIKAP MAHASISWA CALON GURU TERHADAP REPRESENTASI FISIKA - Sirait, Judyanto (Universitas Tanjungpura, 2019)
AbstractÂ Physics concepts can be represented in multiple ways such as verbal, diagrams, graphs, mathematical equations etc. Most previous research focused on drawing and utilizing representations to help students learn physics concepts. This study aims to investigate studentsâ€™ views toward physics representations while solving physics problems by involving preservice physics teachers of two universities in Kalimantan Barat. A physics representation survey was developed to measure studentsâ€™ perception about physics representations. The results show that the majority of the students (above 75%) agree that representations are beneficial for them to understand physics problems and physics concepts and also to find out the best solution of a problem. Some of the students say that they remain provide representations while solving a problem even though there is no extra credit given by instructors. Some of the students feel that they face impediment to grasp representations provided in some physcis text book.Keywords: physics representations, views